2020
DOI: 10.21203/rs.3.rs-23410/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rural-urban differences in the mental health of perinatal women: a UK-based cross-sectional study

Abstract: Background: International data suggest that living in a rural area is associated with an increased risk of perinatal mental illness. This study tested the association between rurality and risk for two mental illnesses prevalent in perinatal women - depression and anxiety. Methods: Using a cross-sectional design, antenatal and postnatal women were approached by healthcare professionals and through other networks in a county in Northern England (UK). After providing informed consent, women completed a questionna… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In contrast, there were no statistically significant difference between rural and urban women who had experienced anxiety (48% versus 50%, respectively; P = 0.82). In this sense, a studies [26,27] has shown that Risk for depression and/or anxiety was found to be higher in the rural group.…”
Section: Plos Onementioning
confidence: 91%
“…In contrast, there were no statistically significant difference between rural and urban women who had experienced anxiety (48% versus 50%, respectively; P = 0.82). In this sense, a studies [26,27] has shown that Risk for depression and/or anxiety was found to be higher in the rural group.…”
Section: Plos Onementioning
confidence: 91%